Ag85A-specific CD4+ T cell lines derived after boosting BCG-vaccinated cattle with Ad5-85A possess both mycobacterial growth inhibition and anti-inflammatory properties. Issue 20 (11th May 2018) - Metcalfe, Hannah J.; Biffar, Lucia; Steinbach, Sabine; Guzman, Efrain; Connelley, Tim; Morrison, Ivan; Vordermeier, H. Martin; Villarreal-Ramos, Bernardo
Highlights: BCG-primed, Ad5-85A boosted cattle present Ag85A specific mycobacteriocidal T cells. Along with mycobacteriocidal activity Ad5-85A boosting induces IL-10 transcription. Ad5-85A boosting does not alter the transcription pattern of pro-inflammatory cytokines. Abstract: There is a need to improve the efficacy of the BCG vaccine against human and bovine tuberculosis . Previous data showed that boosting bacilli Calmette-Guerin (BCG)-vaccinated cattle with a recombinant attenuated human type 5 adenovirally vectored subunit vaccine (Ad5-85A) increased BCG protection and was associated with increased frequency of Ag85A-specific CD4 + T cells post-boosting. Here, the capacity of Ag85A-specific CD4 + T cell lines – derived before and after viral boosting – to interact with BCG-infected macrophages was evaluated. No difference before and after boosting was found in the capacity of these Ag85A-specific CD4 + T cell lines to restrict mycobacterial growth, but the secretion of IL-10 in vitro post-boost increased significantly. Furthermore, cell lines derived post-boost had no statistically significant difference in the secretion of pro-inflammatory cytokines (IL-1β, IL-12, IFNγ or TNFα) compared to pre-boost lines. In conclusion, the protection associated with the increased number of Ag85A-specific CD4 + T cells restricting mycobacterial growth may be associated with anti-inflammatory properties to limit immune-pathology.